2021
DOI: 10.1186/s12885-021-08237-1
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TNFα induces senescence, autophagy and mitochondrial dysfunctions in melanoma cells

Abstract: Background Tumor necrosis factor alpha (TNFα) is a pleiotropic cytokine with both anti-tumorigenic and pro-tumorigenic activity, affecting tumor cell biology, the balance between cell survival and death. The final effect of TNFα is dependent on the type of malignant cells, with the potential to arrest cancer progression. Methods In order to explain the diverse cellular response to TNFα, we engineered melanoma and colorectal carcinoma cell lines sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…84 Second, TLR4 activation in cells can impact the expression of various inflammatory cytokines, including TNFα and IL-6, 85 ultimately leading to alterations in mitochondrial status, decreased ATP production, and changes in mitochondrial morphology. 86,87 We observed an increase in TLR4, NFκB, TNFα, and IL-6 levels in both blood and the gastrocnemius muscle due to Dityr treatment. Dityr exposure also significantly increased the protein level of NFκB in both the cytoplasm and nucleus.…”
Section: Discussionmentioning
confidence: 76%
“…84 Second, TLR4 activation in cells can impact the expression of various inflammatory cytokines, including TNFα and IL-6, 85 ultimately leading to alterations in mitochondrial status, decreased ATP production, and changes in mitochondrial morphology. 86,87 We observed an increase in TLR4, NFκB, TNFα, and IL-6 levels in both blood and the gastrocnemius muscle due to Dityr treatment. Dityr exposure also significantly increased the protein level of NFκB in both the cytoplasm and nucleus.…”
Section: Discussionmentioning
confidence: 76%
“…We postulate that the attenuated signal transduction triggered by TNF-α is a consequence of the reduced expression of the TRAF1 and TNFRSF9 receptors. Tyciakova observed that TNF-α overexpression is accompanied by a significant upregulation of the proinflammatory cytokine IL-6 gene in A375 melanoma cells and proapoptotic ligand TRAIL gene in colorectal cancer cell HT29, both of which were mediated by TNF-α/TNFR1 signaling (Tyciakova et al 2021 ). On the contrary, our study suggests that RIPK4 may regulate IL-8 expression by involving in the MAPK kinase cascade and NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…In senescent cells, mitochondrial alterations such as fragmentation in the mitochondrial network or loss in the Δψ are common features [ 52 , 53 ]. Our results coincide with those reported in colon and melanocyte cell lines exposed to overexpression of TNF-α, which decreased the Δψ and increased the fragmentation of the mitochondrial network.…”
Section: Discussionmentioning
confidence: 99%
“…Our results coincide with those reported in colon and melanocyte cell lines exposed to overexpression of TNF-α, which decreased the Δψ and increased the fragmentation of the mitochondrial network. After an early process of apoptosis, the remaining cells show mitochondrial dysfunction and increased cytokine expression, which is associated with cellular senescence [ 53 ]. The evidence on altered mitochondrial dynamics and cellular senescence is under discussion because the results may vary depending on the cell type under study [ 22 , 54 ].…”
Section: Discussionmentioning
confidence: 99%